Brief Report: Circulating Markers of Immunologic Activity Reflect Adiposity in Persons With HIV on Antiretroviral Therapy. (1st September 2018) - Koethe, John R.; Jenkins, Cathy A.; Furch, Briana D.; Lake, Jordan E.; Barnett, Louise; Hager, Cindy C.; Smith, Rita; Hulgan, Todd; Shepherd, Bryan E.; Kalams, Spyros A.
Abstract : Background: Obesity alters adipose tissue immunology, and these changes may be reflected in circulating soluble inflammatory biomarker and T-cell subset profiles measured in HIV research studies. Methods: We recruited 70 adults with HIV (50% obese) on efavirenz, tenofovir, and emtricitabine, virologic suppression for >2 years, and no rheumatologic or other known inflammatory conditions. We measured fasting plasma levels of several markers of innate immunity and major CD4 + and CD8 + T-cell subsets. We assessed relationships between measurements of total adiposity [body mass index (BMI), dual-energy X-ray absorptiometry-quantified fat mass index (FMI), and plasma leptin] and the immunologic parameters using covariate-adjusted Spearman's rank correlations. Results: The cohort was 43% women, 54% nonwhite, and median age was 45 years. Higher BMI, FMI, and plasma leptin were consistently associated with higher C-reactive protein, serum amyloid A, and interleukin-6 ( P < 0.01 for all), but lower interleukin-10 ( P ⩽ 0.02 for all). BMI and FMI were positively associated with soluble tumor necrosis factor-α receptor 1 levels ( P ⩽ 0.02 for both), and a positive correlation approached significance for all 3 body composition measurements with soluble CD163 ( P ⩽ 0.09 for all). Higher BMI and FMI were associated with lower CD38 expression on CD4 + T cells ( P ⩽ 0.04 for both), but higher CD69 expression ( P ⩽ 0.01 for BMI and FMI, P = 0.07 for leptin). Conclusions: Greater adiposity is associated with alterations in a limited set of circulating immune markers, potentially reflecting changes known to occur in adipose tissue with treated HIV infection. Measuring total fat mass radiographically did not yield substantively different results compared with BMI. Abstract : Supplemental Digital Content is Available in the Text.